2009
DOI: 10.1038/nature07674
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T-cell suppressor program co-opts transcription factor IRF4 to control TH2 responses

Abstract: In the course of infection or autoimmunity, particular transcription factors orchestrate the differentiation of T H 1, T H 2 or T H 17 effector cells, the responses of which are limited by a distinct lineage of suppressive regulatory T cells (T reg ). T reg cell differentiation and function are guided by the transcription factor Foxp3, and their deficiency due to mutations in Foxp3 results in aggressive fatal autoimmune disease associated with sharply augmented T H 1 and T H 2 cytokine production [1][2][3] . R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
766
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 838 publications
(796 citation statements)
references
References 31 publications
28
766
2
Order By: Relevance
“…However, it is not clear whether such Treg cells have intrinsically different suppressive function or whether they share common suppressive properties and the specificity is exerted mainly through local environmental adaptation. The latter hypothesis is supported by the observations that Treg cells isolated from these studies largely show intact suppressive activity in vitro (9)(10)(11)(12). We sought to approach this question by addressing whether transcriptionally diverse Treg cell subsets exist in humans, and whether the diversity accounts for potential differences in their in vitro functionality.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…However, it is not clear whether such Treg cells have intrinsically different suppressive function or whether they share common suppressive properties and the specificity is exerted mainly through local environmental adaptation. The latter hypothesis is supported by the observations that Treg cells isolated from these studies largely show intact suppressive activity in vitro (9)(10)(11)(12). We sought to approach this question by addressing whether transcriptionally diverse Treg cell subsets exist in humans, and whether the diversity accounts for potential differences in their in vitro functionality.…”
Section: Discussionmentioning
confidence: 91%
“…Several key studies have revealed a biased breakdown of tolerance when Treg cells are genetically mutated for particular genes. Specifically, Tregspecific deletion of T-bet, IFN regulatory factor 4, Stat3, and Bcl6 resulted in the impairment of specific regulation of Th1, Th2, Th17, and T follicular helper cells, respectively (9)(10)(11)(12). The finding that the key transcription factors for Th cell differentiation are also required for Treg cells to suppress these Teff cells suggests that the Treg population comprises multiple functional subsets, some of which may have a designated Th cell target.…”
Section: R Egulatory T (Treg) Cells Play a Key Role In Maintainingmentioning
confidence: 95%
“…17 On the other hand, the methylbinding domain protein Mbd2 works reversely on CNS2 methylation and plays an important role in promoting CNS2 demethylation and FOXP3 expression. 18 In humans, CD4 19,20 There is also substantial data that suggest how [21][22][23] Additionally, Jinfang Zhu and colleagues confirmed that Tbet 1 Treg cells were able to convert into GATA3 1 Treg cells, and vice versa, which suggests that Th subset-specific reprogramming is a dynamic process. 24 STABILITY AND PLASTICITY OF FOXP3 1 TREG CELLS The topic of Treg cell lineage stability and plasticity has been controversial for many years.…”
Section: Heterogeneity Of Treg Cellsmentioning
confidence: 90%
“…13,14 In addition, Treg-specific deletion of the transcription factors IRF4 (interferon regulatory factor 4) or STAT3 (signal transducer and activator of transcription 3) resulted in an impaired regulation of Th2-and Th17-dominated immune responses, respectively. 15,16 Recently, a population of germinal center-resident Tregs, termed follicular regulatory T cells, was identified. 17,18 These follicular regulatory T cells suppress germinal center B and T cells and depend, similar to their follicular T helper cell counterparts, on the expression of the transcription factor Bcl6 for their development.…”
Section: Introductionmentioning
confidence: 99%